2016
DOI: 10.1111/cen.13022
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the GR and HSD11B1 genes influence body mass index and weight gain during hormone replacement treatment in patients with Addison's disease

Abstract: The BclI polymorphism of the GR gene and the rs4844880 of the HSD11B1 gene may contribute to weight gain and may affect the individual need of glucocorticoid substitution dose in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, our previous analysis conducted in patients with primary adrenal failure who require lifelong glucocorticoid substitution, revealed that HSD11B1 rs3753519 was associated with BMI and fasting plasma glucose, whereas rs12086634 appeared associated with circulating cholesterol [38]. Analogous findings with regard to rs4844880, BMI and weight gain during glucocorticoid replacement were reported in a smaller Hungarian cohort of subjects with adrenocortical insufficiency [39]. These patients are usually treated with hydrocortisone, identical with the natural cortisol molecule, but its proper dosage, mimicking natural diurnal rhythm of cortisol secretion, remains a challenging issue.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, our previous analysis conducted in patients with primary adrenal failure who require lifelong glucocorticoid substitution, revealed that HSD11B1 rs3753519 was associated with BMI and fasting plasma glucose, whereas rs12086634 appeared associated with circulating cholesterol [38]. Analogous findings with regard to rs4844880, BMI and weight gain during glucocorticoid replacement were reported in a smaller Hungarian cohort of subjects with adrenocortical insufficiency [39]. These patients are usually treated with hydrocortisone, identical with the natural cortisol molecule, but its proper dosage, mimicking natural diurnal rhythm of cortisol secretion, remains a challenging issue.…”
Section: Discussionmentioning
confidence: 52%
“…Thirty-one GR loss-of-function mutations have been associated with a glucocorticoid resistance syndrome (MIM#615962) (13,23,24,25), while 33 index cases have been reported (13,23,24). These mutations are summarized in Table 1 and depicted in Fig.…”
Section: Nr3c1 Mutationsmentioning
confidence: 99%
“…Genotyping of the BclI, N363S, and A3669G polymorphisms was performed in peripheral blood DNA isolated with commercially available DNA Isolation Kit (QIAamp DNA Blood Mini Kit (QiampDNA Blood Kit, Qiagen, USA). Genotypes for the BclI and the N363S variants were determined by allelespecific polymerase chain reaction (PCR) as earlier reported [11][12][13]. Genotypes for the A3669G polymorphism were analysed using a primer-probe set purchased as predesigned Taqman allelic discrimination assay according to the manufacturer's instructions (Applied Biosystems, Applied Biosystems Group 850 Lincoln Center Drive Foster City, CA) on a 7500 Fast Real-Time PCR System (Applied Biosystems).…”
Section: Dna Extraction and Genotyping Of Gr Gene Polymorphismsmentioning
confidence: 99%